Short-Term Outcomes of Cataract Surgery in Patients with a History of Central Serous Chorioretinopathy - Jeon Young Joon; Jae Hui Kim; Jong Woo Kim; Chul Gu Kim (Journal of Ophthalmology)
Purpose. This study aimed to evaluate the short-term outcomes of cataract surgery in patients with a history of idiopathic central serous chorioretinopathy (CSC). Methods. This retrospective study included 26 patients with a history of CSC who underwent uncomplicated phacoemulsification and intraocular lens implantation. The best-corrected visual acuity (BCVA) and central foveal thickness (CFT) measured before the surgery were compared with those obtained at mean 3.6 months after the surgery. BCVA outcome was also analyzed in eyes with and without subretinal fluid (SRF). Results. The mean logarithm of the minimal angle of resolution BCVA significantly improved from 0.52 ± 0.40 before the surgery to 0.21 ± 0.30 one month after the surgery and 0.20 ± 0.31 at 3.6 months after the surgery (P<0.001). The mean CFT was 281.2 ± 84.2 μm before the surgery, 301.5 ± 90.7 μm one month after the surgery, and 279.9 ± 83.6 μm at 3.6 months after the surgery. The CFT before surgery was not different from those measured at 3 months (P=0.253). Significant improvement in BCVA at 3.6 months was noted in the SRF group (N = 12, P=0.003) and the non-SRF group (N = 14, P=0.001). CSC recurrence was noted in 2 patients in the non-SRF group. Conclusions. Significant improvement in visual acuity was noted after cataract surgery in patients with a history of idiopathic CSC, without a risk of aggravation of CSC in most patients.